Relationship between biochemical properties of some date varieties and nutritional requirements of Ectomyelois ceratoniae Zeller (1839) - Krid, Keltoum; Djellabi, Nesrine (Algerian Journal of Biosciences, 2022)
Ectomyelois ceratoniae Z is one of the most dangerous insects in the world and Algerian phoeniciculture. The survival of this insect is based on the search for the appropriate dates varieties to its nutritional needs. In this paper, an experimental study was performed to determine these nutritional needs and the mechanisms to obtain them from dates. In this study, three susceptible varieties to the moth attack were chosen, the healthy and infested dates were separated to calculate on the one hand the attack rate and to carry out the qualitative analyzes. The results showed that the moth selects the appropriate dates to lay its eggs and feed the larvae based on the consistency of the dates and their high sucrose content. The content of the sucrose is reduced in attacked dates, resulting from their consumption after the enzymatic degradation by Invertase for the synthesis of simpler sugars (fructose and glucose) to be easily used by the larvae. The more the medium is very acidic (infested dates), the more the degradation of sucrose is important. The total sugar is also necessary to produce sufficient energy for the biological activities of the moth (growth).The use of these organic elements by the larvae leads to a reduction in the weight of the date and increases its fragility.